Hubungan Pengetahuan Ibu Menyusui Dengan Pemberian Kolostrum di Wilayah Kerja Puskesmas Pargarutan Tapanuli Selatan Tahun 2023 - Asni Asni; Erin Padilla Siregar; Amelia Erawaty Siregar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
.Breast milk is the best food for babies, but mothers often fail to breastfeed or stop breastfeeding earlier than they should. Knowledge is necessary during the postpartum period, especially knowledge about the benefits of colostrum in order to achieve success in breastfeeding and avoid misunderstandings about nutrition for babies. At the beginning of feeding, that is, in the first days when breast milk is released, a liquid that is yellow or clear will come out, which is The best quality baby food is to find out the relationship between the level of knowledge of breastfeeding mothers about colostrum and their provision. Colostrum is breast milk that comes out from the first day to the 4th day. Colostrum is a golden liquid, a protective fluid that is rich in anti-infective substances and high in protein. This liquid is yellow in color or can also be clear and is more like blood than milk, because it contains living cells that resemble white blood cells which can kill disease germs. This research uses a descriptive research design with a cross sectional approach to study the relationship between the level of knowledge of breastfeeding mothers about colostrum at the Pargarutan Community Health Center. South Tapanuli The number of samples used in this research was 30 people, of the 30 respondents it can be seen that there were 24 respondents (80%) who had insufficient knowledge about giving colostrum with 17 respondents (56.7%) not giving colostrum and 7 respondents ( 23.3%) gave colostrum, and those who had good knowledge about giving colostrum with 6 respondents (20%) where all respondents gave colostrum. Fisher's exact p value was 0.035 < 0.05. The need for education to pregnant women about breast milk and Colostrum and breastfeeding mothers are expected to provide breast milk at the beginning of life